The role of pH in aqueous photocatalytic oxidation of β-estradiol - Tatyana Malygina; Sergei Preis; Juha Kallas (International Journal of Photoenergy)
Experimental studies of aqueous photocatalytic oxidation (PCO) of β-estradiol in TiO2 suspensions were undertaken. The dependence of PCO efficiency and adsorption of β-estradiol on pH was studied. It was found that both the adsorption of β-estradiol and the PCO efficiency increased practically linearly with increasing concentration of OH-ions. The predominant role of direct β-estradiol oxidation with positively charged holes was thus indirectly confirmed.